IDIOM ABURA (MINYAK) DALAM BAHASA JEPANG - Silvia Kartika Dewi Santoso; Arza Aibonotika; Zuli Laili Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know about the idiom and metaphor from phrases that used abura (oil). The phrases research data used abura word that obtained from Reikai Kanyouku Jiten dictionary and Koujien Japanese-Japanese dictionary, and the sample data obtained from www.kotonoha.gr.jp/shonagon/ and www.aozora.gr.jp/. The theory used in the idiom analysis is semantic theory from Dedi Sutedi (2011) about metaphor from Lakoff and Johnson (1980). The result of this study are phrases that used abura word only one and no one has simultaneously form. There are seven phrases abura which are form of idioms and are phrases for metaphorical form.Key Words : Idiom, metaphor, abura